2019
DOI: 10.1021/acs.analchem.9b01309
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Differential Ion Mobility Separations/Orbitrap Mass Spectrometry without Buffer Gas Limitations

Abstract: Strong orthogonality between differential ion mobility spectrometry (FAIMS) and mass spectrometry (MS) makes their hybrid a powerful approach to separate isomers and isobars. Harnessing that power depends on high resolution in both dimensions. The ultimate mass resolution and accuracy are delivered by Fourier Transform MS increasingly realized in Orbitrap MS, whereas FAIMS resolution is generally maximized by buffers rich in He or H 2 that elevate ion mobility and lead to prominent non-Blanc effects. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 64 publications
(188 reference statements)
0
47
0
Order By: Relevance
“…Using methanol as an added modifier to N 2 as carrier gas, we already showed baseline separation of isomeric ions could be obtained in the case of sarcosine, α-and β-alanine, 44 as well as for the α-, β-, and -aminobutyric acid isomers. 45 As reported in the literature, adding of a fraction of He to the carrier gas 20,22,29 or increasing the waveform amplitude 21 should also be considered for high resolution DMS. Quantification of AAs and related compounds were achieved using our 3D quadrupole ion trap despite the intrinsic limitations of these instruments in terms of sensitivity and linear dynamic range.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using methanol as an added modifier to N 2 as carrier gas, we already showed baseline separation of isomeric ions could be obtained in the case of sarcosine, α-and β-alanine, 44 as well as for the α-, β-, and -aminobutyric acid isomers. 45 As reported in the literature, adding of a fraction of He to the carrier gas 20,22,29 or increasing the waveform amplitude 21 should also be considered for high resolution DMS. Quantification of AAs and related compounds were achieved using our 3D quadrupole ion trap despite the intrinsic limitations of these instruments in terms of sensitivity and linear dynamic range.…”
Section: Discussionmentioning
confidence: 99%
“…30 DMS has also been shown to be more orthogonal to MS/MS than DT-IMS or related time-separation methods, in the case of peptides, for example. 20,31 Coupled to MS/MS, it was shown that the coverage achieved with the DMS is comparable to that achieved with the chromatographic methods. 32 DMS hyphenated to MS/MS has thus been used for analysis of complex biological fluids such as urine and plasma, and especially for the separation of co-eluting isomers.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, in the high‐resolution planar FAIMS, a periodic asymmetric high voltage waveform, defined as dispersion voltage (DV), was applied to one of the two parallel planar electrodes to create an asymmetric alternating electric field ( E D ) in a gap between the two electrodes 21,22 . During each waveform cycle, ions carried by a constant gas flow into the FAIMS gap will be deflected toward either one of electrodes and eventually discharged on the electrodes after many waveform cycles 21–24 . A proper DC compensation voltage (CV) is superimposed on the DV to make ions move in the opposite direction, which can just offset the deflection of ions caused by DV.…”
Section: Introductionmentioning
confidence: 99%
“…A proper DC compensation voltage (CV) is superimposed on the DV to make ions move in the opposite direction, which can just offset the deflection of ions caused by DV. By this way, ions with the specific Δ K ( E ) can be kept stable in the FAIMS gap, which are subsequently carried by the gas out of the FAIMS 23–25 . A FAIMS spectrum of ions with different Δ K ( E ) can be obtained by scanning the CV across a certain voltage range at a given speed 24,25 …”
Section: Introductionmentioning
confidence: 99%